Posttraumatic Lymphedema after Open Fractures of the Lower Extremity—A Retrospective Cohort Analysis - Johannes Maximilian Wagner (MDPI AG, 2021)
Secondary lymphedema is a very common clinical issue with millions of patients suffering from pain, recurrent skin infections, and the constant need for a decongestive therapy. Well-established as a consequence of oncologic procedures, secondary lymphedema is also a well-known phenomenon after trauma. However, precise epidemiological data of lymphedema progress upon severe extremity injuries are still missing. In the present work, we analyzed a patient cohort of 94 individuals who suffered open fractures of the lower extremity and soft tissue injury, of 2nd and 3rd grade according to Tscherne classification, between 2013 and 2019. Typical symptoms of lymphedema have been obtained via interviews and patient medical records in a retrospective cohort analysis. Of all patients, 55% showed symptoms of secondary lymphedema and 14% reported recurrent skin infections, indicating severe lymphedema. Furthermore, comparing patients with and without lymphedema, additional parameters, such as obesity, total number of surgeries, infections, and compartment syndrome, related to lymphedema progress could be identified. According to these data, posttraumatic secondary lymphedema has a highly underestimated clinical prevalence. Further prospective studies are needed to validate this first observation and to identify high-risk groups in order to improve patient’s health care.